Bioaugmented Hydrogen Production from Lignocellulosic Substrates Using Co-Cultures of Shigella flexneri str. G3 and Clostridium acetobutylicum X9 - Gao, Lingfang; Varrone, Cristiano; Sheng, Tao; Liu, Chong; Chen, Chuang; Liu, Wenzong; Wang, Aijie (Journal of Technology Innovations in Renewable Energy, 2014)
Bioaugmented fermentation of cellulosic substrates to produce biohydrogen via co-culture of isolated strains was investigated. Two mesophilic anaerobic bacterial strains, known for their ability to hydrolyze cellulosic substrates, were taken in consideration: Shigella flexneri str. G3, which shows high cellulolytic activity but cannot ferment oligosaccharides to bioenergy, and Clostridium acetobutylicum X9, able to convert microcrystalline cellulose into hydrogen. The ability of the selected strains to effectively convert different cellulosic substrates to hydrogen was tested on carboxymethyl cellulose (AVICEL), as well as pretreated lignocellulosic material such as Bermuda grass, corn stover, rice straw, and corn cob. Results showed that co-culture of Shigella flexneri str G3 and Clostridium acetobutylicum X9 efficiently improved cellulose hydrolysis and subsequent hydrogen production from carboxymethyl cellulose. Hydrogen production yield was enhanced from 0.65 mol H2 (mol glucose)−1 of the X9 single culture to approximately 1.5 mol H2 (mol glucose)−1 of the co-culture, while the cellulose degradation efficiency increased from 50% to 95%. Co-culture also efficiently improved hydrogen production from natural lignocellulosic materials (which was up to 4-5 times higher than mono-culture with X9), with the highest performance of 24.8 mmol L-1 obtained on Bermuda grass. The results demonstrate that co-culture of S. flexneri G3 and C. acetobutylicum X9 was capable of efficiently enhance cellulose conversion to hydrogen, thus fostering potential biofuel applications under mesophilic conditions.